Case of neuromyelitis optica with recurrent stomach carcinoma. Issue 4 (9th October 2017) - Takewaki, Daiki; Kasai, Takashi; Itoh, Kyoko; Shiga, Kensuke; Tokui, Masafumi; Tanaka, Akihiro; Noto, Yu‐ichi; Ohara, Tomoyuki; Mizuno, Toshiki
Abstract: Background: Neuromyelitis optica (NMO) is an autoimmune astrocytopathy associated with anti‐aquaporin‐4 (AQP4). The development of NMO in the setting of cancer suggests that AQP4 autoimmunity might in some cases be paraneoplastic. Case presentation: We report an 85‐year‐old woman who developed a right optic neuritis and a longitudinally extensive transverse myelitis associated with AQP4 autoantibodies after the relapse of stomach cancer. Histopathological observations in several case reports have led to the hypothesis that the NMO associated with the malignancy is caused by an autoimmunity against abnormally expressed AQP4 on tumor cells. However, we found no AQP4 antigen on the cancer cells in our resected tissues. Our findings did not support the concept of a paraneoplastic process in the narrow sense. Conclusions: The exact mechanisms of cancer‐related NMO, which might be multifactorial, remain controversial. Abstract : The development of NMO in the setting of cancer suggests that AQP4 autoimmunity may in some cases be paraneoplastic. Histopathological observations in several case reports have led to the hypothesis that the NMO associated with the malignancy is caused by an autoimmunity against abnormally expressed AQP4 on tumor cells, but we found no AQP4 antigen on the cancer cells in our resected tissues. The exact mechanisms of cancer‐related NMO, which may be multifactorial, remain controversial.